Tunable Single-Photon Scattering of a Giant Λ-type Atom in a SQUID-Chain Waveguide - Zou, Jian-Ping; Gong, Rui-Yang; Xiang, Ze-Liang (Frontiers in Physics, 2022)
We study single-photon scattering of an artificial giant Λ-type atom coupled to a superconducting quantum interference device (SQUID) chains waveguide at two points. In this circuit, the single-photon scattering rates are dependent on the atom-waveguide coupling strengths and the phase accumulated between two coupling points. By modulating the flux-dependent phase velocity in the SQUID-chain waveguide, the photon’s traveling time is changed, and the accumulating phase is adjusted simultaneously. We investigate the relationship between the scattering effect and the flux bias, which allows us to explore novel phenomena with the tunable traveling time in both Markovian and non-Markovian regimes, and to design novel quantum technologies such as quantum storage.